Nurses' knowledge and attitude towards children pain management: a multi-site survey study - Efrem Fenta; Simegnew Kibret; Metages Hunie; Tadese Tamire; Denberu Eshetie; Shimelis Seid; Yewlsew Fentie; Eleni Amaha; Tiruwork Desse; Bantayehu Dejen; Keder Essa; Diriba Teshome (Frontiers Media S.A., 2023)
BackgroundAdequate children's pain management is universally considered an ethical obligation. In evaluating and treating children's pain, nurses invest more time and take a leading role. This study aims to evaluate the knowledge and attitudes of nurses towards the treatment of pediatric pain.Materials and MethodsA total of 292 nurses working at four South Gondar Zone hospitals of Ethiopia was surveyed. To gather information from study participants, the Pediatric Nurses' -Knowledge and Attitudes- Survey Regarding Pain (PNKAS) was employed. Frequency, percentage, mean, and standard deviation of the data were used for descriptive analysis, while Pearson correlation, one-way between-groups analysis of variance, and independent-samples t-test were used for inferential analysis.ResultsA large percentage of nurses (74.7%) lacked adequate knowledge and attitudes (PNKAS score <50%) for pediatric pain treatment. The mean ± SD accurate response score of 43.1% ± 8.6% was achieved by nurses. An increase in pediatrics nursing experience was significantly correlated with nurses' PNKAS score (p < 0.001). The mean PNKAS scores of nurses who had official pain management training differed in a statistically significant way as compared to its counterpart (p < 0.001).ConclusionNurses who are working South Gondar Zone of Ethiopia have insufficient knowledge and attitudes towards treatment of pediatric pain. Therefore, pediatric pain treatment in-service training is urgently needed.